The Effect of K-Pop Fanaticism on Social Media Coverage @tanyakanrl’s Twitter Account - Dika Shafitri; Wahyunengsih Wahyunengsih (MUKASI: Jurnal Ilmu Komunikasi, 2023)
In this article, a questionnaire was distributed to 62 respondents to explore the influence of this phenomenon on news at the @tanyarl autobase. The survey results showed that the majority (61.1%) of respondents agreed that this phenomenon has influenced an increase in reporting on the autobase account. This indicates that K-Pop fanaticism has created a shift in focus and news content. Thus, K-Pop fanaticism can contribute positively to the development of a more creative and innovative journalistic style. However, the pressure to produce content that captures the attention of K-Pop fans can lead to sensationalism and a loss of objectivity. Survey results show that some respondents feel that news on Twitter tends to be more subjective and not entirely accurate in its coverage of K-Pop. Additionally, it was also found that K-Pop can disrupt the balance and fairness of attention given to other topics on the platform. The dominance of K-Pop content on social media makes it difficult for other topics to receive the attention they deserve. Therefore, it is necessary to implement fact-checking mechanisms and promote critical thinking among social media users. Educating users about the assessment of news quality and the importance of topic diversity should be enhanced so that users can distinguish between trustworthy and untrustworthy news content.